The Effect of Capital Intensity and Managerial Ownership on Tax Aggressivenesses in the Mining Sector Listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 Period - Zahra, Nazwa; Andrianti, Shinta Siti; Rahman, Azis; Haris, Melisa Putri Sagita (Green Publisher Indonesia, 2025)
This study examines the influence of capital intensity and managerial ownership on tax aggressiveness in mining companies listed on the Indonesia Stock Exchange (Indonesia Stock Exchange (IDX)) for the 2021–2023 period. Tax aggressiveness, measured by the effective tax rate (ETR), represents corporate strategies to minimize tax burdens, which can affect state revenue. Using a quantitative approach with multiple linear regression analysis, data were collected from the financial statements of 26 mining companies selected through purposive sampling. The results show that capital intensity has no significant effect on tax aggressiveness (p > 0.05), indicating that high fixed asset investment does not directly encourage aggressive tax behavior in the mining sector. In contrast, managerial ownership has a significant positive effect (p < 0.05), suggesting that managers with share ownership tend to engage more in tax-saving strategies to enhance after-tax profits. Simultaneously, both variables explain only 6.8% of the variation in tax aggressiveness (R² = 0.068), implying that other factors not included in the model have a stronger influence. These findings contribute to agency theory by highlighting the role of ownership structure in corporate tax decisions and offer practical insights for regulators and investors in monitoring tax-related risks in capital-intensive industries.